HOW DOES THE MARKETING MIX AFFECT INTEREST IN SECTION CESAREA BIRTH DELIVERING AT X HOSPITAL - Boby, Ratna Indrawati, Nofierni (CV. Bunda Ratu, 2023)
This study aims to analyze the marketing environment of interest in giving birth by cesarean sect at X Hospital in Bekasi This study uses a quantitative approach to the influence of Marketing Mix; Product; Price; Place; and Promotion of Interest in Childbirth. In this study using explanatory research with a quantitative approach, and the subjects of the study were all patients at X Hospital in Bekasi as many as 340 patients who gave birth sectio cesarea. This study uses PLS-SEM, the results of the study obtained conclusions on the Effect of Marketing Mix of Childbirth Interest on Sectio Cesarea. Seeing the importance of a positive marketing mix, this study can provide information about things that X Hospital can use in order to improve services to patients and ensure price acceptance still occurs, With positive pricing conditions thus, there is an influence of the Marketing Mix on Childbirth Interest.